Healthcare outcomes and special education eligibility in children with congenital CMV. - Ryan Rochat; Elizabeth Goodman; Jerry Miller; Wei Wang; Gail J Demmler-Harrison (PLoS ONE)
Objectives Congenital cytomegalovirus disease (cCMV) can have significant sensory and neurodevelopmental sequelae throughout childhood. Many of these sequalae are consistent with special education eligibility, but the special education needs of affected children have not been systematically studied. Methods Retrospective chart reviews from two cohorts of cCMV children receiving care in a large tertiary care children's hospital were included in this study: a historical research cohort (N = 186, 41% symptomatic at birth) and a contemporary clinical cohort of cCMV patients (N = 112, 68% symptomatic at birth). SNOMED-CT was used to identify ICD-10 codes describing special education-qualifying health outcomes fitting the Individuals with Disabilities Education Act (IDEA) criteria. ICD-10 codes were retrospectively applied to the historical research cohort through manual chart review, whereas the ICD-10 billing codes were extracted from the electronic medical record for all encounters in the contemporary cohort. Results Of the 56 unique special education-qualifying ICD-10 codes we identified as pertinent to the IDEA, at least one was noted in 39% of those asymptomatic at birth (AcCMV) as compared to 94% of the patients symptomatic at birth (ScCMV). In the contemporary clinical cohort, at least one of these codes was noted in 67% of the AcCMV patients as compared to 95% for ScCMV patients. 61% of patients in the historical and 86% in the contemporary cohort had at least one special education-qualifying ICD-10 code. Developmental, mobility, physical therapy and hearing-related health outcomes were common in both ScCMV and AcCMV patients. Conclusions Health outcomes qualifying for special educational services occur commonly in children with cCMV, including those who are classified as asymptomatic at birth. The emergence of qualifying conditions beyond the neonatal period among these children suggests that continued surveillance of this vulnerable population throughout early childhood may facilitate the timely identification of health outcomes requiring special educational services.